Identification of a novel series of azabenzimidazole-derived inhibitors of spleen tyrosine kinase. Issue 18 (15th September 2020) - Kawatkar, Sameer P.; Barlaam, Bernard; Kemmitt, Paul; Simpson, Iain; Watson, David; Wang, Peng; Lamont, Scott; Su, Qibin; Boiko, Scott; Ikeda, Timothy; Patel, Joe; Pike, Andy; et al.
Graphical abstract: Abstract: Spleen Tyrosine Kinase (SYK) is a well-studied enzyme with therapeutic applications in oncology and autoimmune diseases. We identified an azabenzimidazole (ABI) series of SYK inhibitors by mining activity data of 86, 000 compounds from legacy biochemical assays with SYK and other homologous kinases as target enzymes. A structure-based design and hybridization approach was then used to improve the potency and kinase selectivity of the hits. Lead compound 23 from this novel ABI series has a SYK IC50  = 0.21 nM in a biochemical assay and inhibits growth of SUDHL-4 cells at a GI50  = 210 nM.